Tryptyk – "Grudki kadzidła IV" Andrzeja Nikodemowicza i metafizyka człowieka medytującego - Furtak, Karol (Res Facta Nova, 2022)
The oeuvre of Andrzej Nikodemowicz (1925–2017), a composer born and living until 1980 in Lviv and then in Lublin, is largely seen through the prism of his religious music. This situation influences the interpretations of his works, including those of a secular nature. Hitherto, the oeuvre of Andrzej Nikodemowicz has been discussed in the literature with regard to his early works, works of the cantata genre and concertante works. The author of this article places Nikodemowicz’s cycle composed in 2010 to Beata Obertyńska’s religious poetry Tryptyk: Grudki kadzidła IV at the centre of his interest. First of all, he aims to draw from it an interpretation related to the attitude of a meditating human being (homo meditans), known from the works of the aforementioned poet. In order to accomplish this goal, it is necessary to identify in the musical structure of the cycle ‘hermeneutic windows’ in the character of textual inclusions and structural tropes, and then the interpretative categories to which they might refer the listener. Inspired by Lawrence Kramer’s theory, these categories are presented, on the one hand, as metaphors, referring to the listener’s subjective states, on the other hand, as a set of views and theses of a general nature, which this American musicologist calls metaphysics.